Changing student attitudes, perceptions, and awareness. - Goldberg, J.R (IEEE Engineering in medicine and biology magazine)
Senior design capstone courses provide an excellent opportunity for biomedical engineering design instructors to help students begin to look at the "real world" differently. Depending upon the structure of a particular institution's senior design course and the resulting design experience obtained, students' attitudes and perceptions related to biomedical engineering design, the product development process, and the engineering profession can be positively affected. Therefore, senior design experience provides gateways for course instructors to transform the way students think about the design process, teamwork, expected job performance, and the engineering profession. The resulting changes in attitudes, perceptions, and awareness can play an important role in preparing students for careers in biomedical engineering.